2014
DOI: 10.1590/1413-81232014193.01552013
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao excesso de peso em crianças brasileiras menores de cinco anos

Abstract: Fatores associados ao excesso de peso em crianças brasileiras menores de cinco anosFactors associated with excess weight in Brazilian children under five years of age

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
9
0
8
Order By: Relevance
“…A study based on PNDS -2006 data also revealed higher prevalences of overweight in children under 5 in all Brazilian regions, with the highest percentages in the South (9.3%) and the lowest percentages in the North region (5.1%) 43 .…”
Section: Discussionmentioning
confidence: 93%
“…A study based on PNDS -2006 data also revealed higher prevalences of overweight in children under 5 in all Brazilian regions, with the highest percentages in the South (9.3%) and the lowest percentages in the North region (5.1%) 43 .…”
Section: Discussionmentioning
confidence: 93%
“…The family has a determinant role during the learning process of the alimentation of the children, so that the life habits of the parents, the parenting styles and their interaction with the children are significant for the formation of the infant's eating habits. 5,12,20,21 In the analysis of food consumption, almost all children had main meals daily with the family at home. This finding is important considering that the family has a set of values, beliefs, knowledge and eating habits that may constitute a protective or risk factor for health.…”
Section: Discussionmentioning
confidence: 99%
“…31 Adequate food and nutrition are basic requirements for the integrality of health care. 26 Interventions for the reduction of overweight in children should focus on the family and the household 9,12,32,33 for the promotion of positive parental eating practices, considering the role of parental modeling in children's eating behavior. 32,33 Parents or guardians should be empowered about healthy eating and sensitized about the need to change the family's lifestyle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations